Factors associated with hematuric struvite crystalluria in cats. Issue 10 (October 2019) - Okafor, Chika C; Pearl, David L; Blois, Shauna L; Lefebvre, Sandra L; Yang, Mingyin; Lund, Elizabeth M; Dewey, Cate E
Objectives: The aim of the study was to identify any dietary, signalment, geographic and clinical factors associated with hematuric struvite crystalluria (HSC) in a population of cats that visit general care veterinary hospitals in the USA. Methods: In total, 4032 cats that had a first-time diagnosis of HSC and 8064 control cats with no history of hematuria or crystalluria were identified from medical records of all cats examined between 2007 and 2011 at 790 US veterinary hospitals. Extracted variables included age, sex, neuter status, breed, diet, urinalysis results and history of cystitis. Potential associations between these variables and HSC were estimated. Results: Controlling for other factors, young cats fed a dry diet had an increased likelihood of HSC relative to young cats fed a non-dry diet. However, as age increased, the likelihood of HSC declined for cats fed a dry diet and increased for cats fed a non-dry diet. Moreover, the odds of HSC were significantly greater when cats were unneutered (vs neutered; odds ratio [OR] 45.52) or had a thin (vs heavy) body condition (OR 23.81), diagnosis of cystitis (OR 2.84), urine protein concentration >30 mg/dl (OR 4.72), alkaline (vs neutral) urine pH (OR 3.34), pyuria (OR 23.67) or bacteriuria (OR 2.24). Conclusions and relevance: The present study provides estimates of the strengths of association between HSC and certain signalment and clinical characteristics of cats. This information could help clinicians to perform a more directed screening for struvite crystalluria in certain cat populations. Follow-up studies that build on the findings of this study could explore the clinical importance of HSC in cats.